Cauliflower (Brassica oleracea var. botrytis L) Growth and Yield Response by providing Kasgot Fertilizer and NPK on Ultisol Soil - Raisa Baharuddin; Subhan Arridho; Stephany Gea (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
The development of cauliflower cultivation (Brassica oleracea var. botrytis L.) on marginal land necessitates implementing appropriate cultivation techniques to enhance plant growth and production. In this context, applying organic fertilizers, such as Kasgot and NPK fertilizers, is anticipated to improve the productivity of cauliflower in Riau Province. This study aims to evaluate the effects of Kasgot and NPK fertilizers on the growth and production of cauliflower cultivated on red-yellow podzolic soil. The research was conducted at the UIR Experimental Garden in Pekanbaru from August to December 2024. A Completely Randomized Design (CRD) Factorial was employed for this study. The first factor examined was the dosage of Kasgot fertilizer (K), which included four treatment levels: no Kasgot fertilizer, and Kasgot fertilizer at 100 g, 200 g, and 300 g per polybag. The second factor examined was the NPK fertilizer (N) dose, which included five treatment levels: no NPK, and NPK fertilizer at 3.75 g, 7.5 g, 11.25 g, and 15 g per polybag. Each experimental unit was replicated three times. The results indicated that the data collected, including plant height, age of flower formation, relative growth rate, flower weight per plant, flower diameter, and root volume, were significantly influenced by the interaction between phosphorus fertilizer and NPK fertilizer. The combination of 300 g of Kasgot fertilizer per polybag and 7.25 g of NPK per polybag proved to be the most effective in enhancing the relative growth rate, flower weight per plant, and flower diameter in cauliflower.